New coffee house in the public garden - Zincke, Johann Wenzel, 1797-1858 (engraver):::Creator::::::::::::; Mollo, Tranquillo, 1767-1827 (publisher):::Contributor::::::::::::; Gurk, Eduard, 1801-1841 (artist):::creator:::::::::::: (T. Mollo; Vienna; Austria)
Color engraving with view of coffee house in public garden in Vienna, Austria